Effects of glucose, propionate and splanchnic hormones on neuropeptide mRNA concentrations in the ovine hypothalamus - Relling, Alejandro Enrique (2012)
The capacity for glucose, propionate or hormones of splanchnic origin to influence appetite by directly regulating the expression of neuropeptides in the feeding centres of the hypothalamus of the ruminant is not described. Therefore, our objective was to measure the direct effect of metabolites (glucose and propionate) or hormones [insulin, cholecystokinin (CCK), glucagon-like peptide-1 (GLP-1) and polypeptide YY (PYY)] on hypothalamic mRNA concentrations for neuropeptide Y (NPY), agouti-related peptide (AgRP) and proopiomelanocortin (POMC) following in vitro incubation. Hypothalamic tissue from 4- to 5-month-old lambs was obtained at slaughter and immediately incubated in culture media for 2h at 36°C. Treatments included a control Dulbecco's modified Eagle medium (DMEM) containing 1mm glucose or DMEM with the following additions: 10mm glucose, 1mm propionate, 1nm insulin, 120pm GLP-1, 100pm PYY, 80pm CCK or 10mm glucose plus 1nm insulin. The abundance of mRNA for NPY, AgRP and POMC was measured using quantitative reverse transcriptase PCR. Fisher's protected LSD test was used to compare changes in relative mRNA concentrations for the hypothalamus incubated in the control media vs. the rest of the treatments. The media containing glucose plus insulin increased POMC mRNA concentration (p<0.05), but did not affect NPY or AgRP mRNA concentration. There were no effects observed for the other treatments (p>0.20). Results of the present study are consistent with the concept that effects of propionate on feed intake in ruminants is not mediated through direct effects on the hypothalamus, and that insulin is required for an effect of glucose on hypothalamic POMC expression.